2003
DOI: 10.1080/0269905021000013219
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the self-awareness of deficits interview for adults with traumatic brain injury

Abstract: High test-re-test reliability was demonstrated for both total (ICC = 0.94) and sub-section scores (ICC = 0.85, 0.86 and 0.86). The results, combined with previous research indicating the high inter-rater reliability of the SADI, suggest the SADI is a reliable means of evaluating level of self-awareness. Further research is required to investigate other psychometric properties of the SADI and the two checklists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Patients with memory impairments arising from temporal or diencephalic lesions may notice cues but fail when they endeavour to remember the associated action. As has often been observed [11,24,25] an important aspect of prospective remembering, however, is the way successful completion relies on self-initiated strategic processes, which are often comprised by frontal damage. Some patients, despite having normal memory and attention test scores, may fail a PM test because the strategies they adopt during the task are ineffective.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with memory impairments arising from temporal or diencephalic lesions may notice cues but fail when they endeavour to remember the associated action. As has often been observed [11,24,25] an important aspect of prospective remembering, however, is the way successful completion relies on self-initiated strategic processes, which are often comprised by frontal damage. Some patients, despite having normal memory and attention test scores, may fail a PM test because the strategies they adopt during the task are ineffective.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of severe TBI, constant accurate feedback from significant others, clinicians and personal experiences is necessary for patients to acquire insight into what to expect of themselves. There is considerable evidence to suggest that self-awareness of cognitive changes, including prospective memory dysfunction, is compromised in patients who have experienced a severe TBI [22][23][24][25][26]. Roche et al [24], in a study comparing TBI patients' self-ratings of the frequency of such failures with ratings made by significant others, found that the patients consistently underestimated their level of impairment.…”
Section: Self-awareness and Pmmentioning
confidence: 99%
“…A significant other/ therapist checklist has also been developed in order to gain collateral information to assist scoring [28]. A relative or close friend completed the checklist in the present study as not all participants were in regular contact with a therapist.…”
Section: Methodsmentioning
confidence: 99%
“…A relative or close friend completed the checklist in the present study as not all participants were in regular contact with a therapist. Research investigating the psychometric properties of the SADI has found that the measure had sound inter-rater reliability (0.82) [7] and good test-re-test reliability (0.85-0.94) [28].…”
Section: Methodsmentioning
confidence: 99%
“…These mainly take the form of questionnaires and interviews which are used to compare reports made by patients and significant others. Examples include the Dysexecutive Questionnaire, the SelfAwareness of Deficits Interview (Bogod, Mateer, & MacDonald, 2003;Burgess & Alderman, 1996;Simmond & Fleming, 2003) and the Awareness Questionnaire (Sherer, Bergloff, Boake, High, & Levin, 1998b). Impaired awareness of deficits is a lack of global awareness (i.e., awareness of a general error propensity).…”
Section: Introductionmentioning
confidence: 99%